Respuesta :
Answer:
Step-by-step explanation:
hello :
(x + 1)2 – 9 is equivalent to (x - 2)(x + 4)
because (x + 1)2 – 9 =(x + 1)2 – 3²
= (x+1-3)(x+1+3) =(x-2)(x+4)
Answer:
(x + 1)² - 9
Step-by-step explanation:
Expand each of the factors using FOIL
(x - 2)(x + 4)
= x² + 4x - 2x - 8 ← collect like terms
= x² + 2x - 8
Now consider the expansions of
(x + 1)² - 9
= x² + 2x + 1 - 9
= x² + 2x - 8 ← equivalent to (x - 2)(x + 4)
--------------------------------------------------------------
(x - 1)² - 9
= x² - 2x + 1 - 9
= x² - 2x - 8 ← not equivalent to (x - 2)(x + 4)
-----------------------------------------------------------------
(x + 1)² - 7
= x² + 2x + 1 - 7
= x² + 2x - 6 ← not equivalent to (x - 2)(x + 4)
--------------------------------------------------------------------
(x - 1)² - 7
= x² - 2x + 1 - 7
= x² - 2x - 6 ← not equivalent to (x - 2)(x + 4)